Thermal Ablation of Bone Metastases - Moynagh, Michael R.; Kurup, A. Nicholas; Callstrom, Matthew R. (Seminars in Interventional Radiology, 2018)
Image-guided, minimally invasive, percutaneous thermal ablation of bone metastases has unique advantages compared with surgery or radiation therapy. Thermal ablation of osseous metastases may result in significant pain palliation, prevention of skeletal-related events, and durable local tumor control. This article will describe current thermal ablation techniques utilized to treat bone metastases, summarize contemporary evidence supporting such thermal ablation treatments, and outline an approach to percutaneous ablative treatment.
Keywords: osseous metastases; thermal ablation; cancer pain; interventional radiology; pain palliation